TALK-AND-DETERIORATE (‘TALK-AND-DIE’) AFTER MINOR TRAUMATIC BRAIN INJURY: MECHANISMS, RISKS, AND PREVENTION - Muhammad Kalim Raza; Alkov R.A; Lutfullayev X.Z.; Jabborova M.H. (Web of Journals Publishing, 2026)
The "talk-and-deteriorate" phenomenon represents a critical subset of patients with initially mild traumatic brain injury (TBI) who experience rapid neurological decline after a period of apparent stability. Characterized by an initial Glasgow Coma Scale (GCS) score of 13–15 and a subsequent drop to ≤8, this syndrome often involves a "lucid interval" masking evolving secondary brain injuries, including delayed intracranial hematomas and hemorrhagic progression of contusions. Pathophysiological mechanisms include excitotoxicity, ionic imbalance, inflammation, and coagulopathy, while risk factors such as advanced age, anticoagulant use, and preexisting comorbidities increase susceptibility. Clinical recognition relies on vigilant neurological monitoring, repeat neuroimaging, and timely intervention, with surgical decompression indicated for significant deterioration. Early identification and standardized observation protocols are essential to improve outcomes in this high-risk population.
Keywords: Talk-and-deteriorate phenomenon, mild traumatic brain injury, delayed intracranial hematoma, secondary brain injury, lucid interval, hemorrhagic progression of contusions, neurological deterioration